PEMAHAMAN WIRAUSAHAWAN/WATI KATOLIK TENTANG KERJA MENURUT ENSIKLIk LABOREM EXCERCENS - Gezhara Edith Sabella Ariyuki; Wibowo Singgih (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Work is any human effort made either paid or unpaid, which aim to be accomplished in order to make the world a better place and getting closer to the way God isworking on everything. The Church has issued encyclicals to guide people in the work of one of them is the encyclical Laborem Excercens. How can understanding the Catholic entrepreneur about work? How encyclical Laborem Excercens give an opinion about work? The extent to which there is a match between the opinion Catholic with entrepreneur encyclical Laborem Excercens about work? This study uses a qualitative method which is a form of research that focuses on efforts to examine and understand the attitudes, views, feelings, and behavior of individuals or groups of people about a particular event. This research is head to determined the understanding of Catholic entrepreneur about work. Knowing the encyclical Laborem Excercens view about work. Knowing the extent of compatibility between the opinion of Catholic entrepreneur and encyclical Laborem Excercens about work. The results of this research indicate that all Catholic entrepreneur understanding of the work well. There are an opinions of Catholic entrepreneur about Encyclical Laborem Excercens. One of them ever heard Encyclical Laborem Excercens. Then, nine of them never heard Encyclical Laborem Excercens. Furthermore, although comprehension Catholic entrepreneur about Encyclical Laborem Excercens not understood yet, but actually they have done Encyclical Laborem Excercens. In general it can be said that all Catholic entrepreneurabout work. Related to the encyclical Laborem Excercens Catholic entrepreneurs have never heard but they have done Encyclical Laborem Excercens without aware it.